Five new species of Ectobiidae (Blattodea) collected in the Reserva Ducke, Amazonas, Brazil - Lopes, Sonia Maria; Oliveira, Edivar Heeren de; Tarli, Vitor Dias (Biota Neotropica, 2014)
Herein we describe five new species of the Ectobiidae subfamilies Pseudophyllodromiinae (Amazonina spiculata sp. nov., Amazonina spinostylata sp. nov., Cariblatta duckeniana sp. nov., Cariblatta manauensis sp. nov.) and Nyctiborinae (Nyctibora nigra sp. nov.), collected in the Reserva Ducke, Manaus, state of Amazonas. The specimens were collected from litter, fallen logs, branches, and foliage. We illustrate the male genitalia of the new species. © 2014, Universidade Estadual de Campinas UNICAMP. All rights reserved.
Cinco espécies novas de Ectobiidae (Blattodea) coletados na Reserva Ducke, Amazonas, Brasil
Keywords: Blattaria; Nyctibora; Spiculata